Smoking and blood pressure levels in hypertensive patients: evaluating the role of gender, age and hypertension duration - Siddiqui, Jameel Ahmed; Zaidi, Syed aijaz; Iqbal, Jawed; Qamar, Nazia; Adil, Rahila; Ahmed, Anam; Arif, Madiha; Anwar, Adnan (International Journal of Research in Medical Sciences, 2019)
Background: Hypertension is estimated to affect about 40% of adults above 25 years of age globally. While many of the risk factors of hypertension are well known, such is not the case with smoking. Pertinent published literature is heterogeneous, with a dearth of relevant local data. Objectives was to study the relationship between smoking and blood pressure levels in hypertensive patients and to assess the effects of gender, age and hypertension duration on such a relationship. Methods: A cross-sectional study was carried out on a total of 298 conveniently sampled patients, aged 18 or above, from the medical outpatient department of a secondary care hospital of Karachi. The relevant data were collected by means of a structured questionnaire whereas the blood pressure level was checked using sphygmomanometer with stethoscope. Mann Whitney U test was used for inferential analysis whereas the significance level was set at 0.05. Results: Overall, both the systolic and diastolic blood pressure levels were significantly associated with smoking history (p<0.05 for both) where they were found to be higher in smokers than in non-smokers. Furthermore, after gender, age and hypertension duration based stratifications; both the systolic and diastolic blood pressure levels were still significantly associated with smoking history in patients who were male, were ≥35 years old and had <5 years hypertension duration (p<0.05 for both) where they were again found to be higher in smokers than in non-smokers. Conclusions: The study results showed a significant association of positive smoking history with higher mean systolic and diastolic blood pressure levels, though after stratifying for gender, age and hypertension duration, this relationship persisted only in patients who were male, were ≥35 years old and had <5 years hypertension duration.